2021
DOI: 10.15439/2021f3
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Solution to Handling Randomness and Imperfect Information in Monte Carlo Tree Search

Abstract: This paper provides practical guidelines for developing strong AI agents based on the Monte Carlo Tree Search algorithm in a game with imperfect information and/or randomness. These guidelines are backed up by series of experiments carried out in the very popular game -Hearthstone. Despite the focus on Hearthstone, the paper is written with reusability and universal applications in mind. For MCTS algorithm, we introduced a few novel ideas such as complete elimination of the so-called nature moves, separation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…[ 39–41 ] The action at a high level is not well understood, although traditional studies have demonstrated excellent performance in solo maneuvers or progressed to simple navigation scenarios. [ 11,42–44 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 39–41 ] The action at a high level is not well understood, although traditional studies have demonstrated excellent performance in solo maneuvers or progressed to simple navigation scenarios. [ 11,42–44 ]…”
Section: Introductionmentioning
confidence: 99%